Masyarakat Multikultural: Konsepsi, Ciri dan Faktor Pembentuknya - Ifa Nurhayati; Lina Agustina (Akademika, 2020)
Indonesia is widely known as a plural society in addition to popularly being a multicultural nation. Not only does it have the wealth of natural resources, but also it has the most vibrant socio-cultural wealth in the world. This cultural diversity becomes an inevitable reality. Thus looking at the concept of multicultural society, it is as relevant as an epistemic basis that Indonesian people could live together, but at the same time have the potential for possible "civil war". This paper discussed the characteristics of multicultural societies having become the social reality of Indonesia in addition to explaining the formation of multi-cultural society. This study also found that multiculturality of the community was formed due to such factors as geographical, influences on foreign cultures, different climatic conditions, diversity of ethnic groups, and religious and racial diversity.